The predicted effect of climate change on indoor overheating of heritage apartments in two different Chinese climate zones. Issue 7 (August 2022) - Lei, Muxi; van Hooff, Twan; Blocken, Bert; Pereira Roders, Ana
Understanding the effects of climate change on building indoor thermal conditions is of importance for providing a comfortable thermal environment for occupants. Some multi-family dwellings have already been listed as heritage in China (hereinafter referred to as heritage apartments), limiting modifications to the building envelope. However, the effect of climate change on thermal comfort in heritage apartments with a compact interior (i.e. without a living room) built before the 1980s in different Chinese climate zones has seldom been studied. This study focuses on the current and future thermal comfort in two-bedroom heritage apartments in China. The study was conducted for two different Chinese climate zones, that is, a cold climate zone (Beijing), and a hot summer and cold winter climate zone (Shanghai) and both current climate scenarios (typical meteorological years) and future climate scenarios (2050) were used. The results indicate, among other things, increases of 58%–60% and 41%–44% in the predicted average number of overheating hours in 2050 compared to the current climate for the studied bedrooms on the first floor in dwellings in Beijing and Shanghai, respectively.